2016
DOI: 10.1136/jclinpath-2016-203879
|View full text |Cite
|
Sign up to set email alerts
|

Haemoglobinopathies that occur with decreased HbA2levels: a gene mutation set involving the δ gene at a Spanish centre

Abstract: HbA is an essential parameter in the diagnostics of haemoglobinopathies. HPLC-EC and CZE allow the quantification of HbA. Here, we show that quantification of HbA is critical for the identification of α, δ and βδ thalassaemias. Structural variants are discovered by HPLC. Molecular genetics is required for the proper identification of the mutations. Only with this knowledge is genetic counselling possible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…The widespread use of capillary electrophoresis in routine laboratory test to separate and quantify Hb fractions facilitated the diagnosis of δ‐thalassemia (Villegas et al, ). The frequency of δ‐thalassemia in the Yunnan population is 0.49%, which is higher than other populations in Southern China (0.4%, 152/40,863) (Liu et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The widespread use of capillary electrophoresis in routine laboratory test to separate and quantify Hb fractions facilitated the diagnosis of δ‐thalassemia (Villegas et al, ). The frequency of δ‐thalassemia in the Yunnan population is 0.49%, which is higher than other populations in Southern China (0.4%, 152/40,863) (Liu et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…We also evaluated the HbA2 levels in individuals without SCT to analyse α-thalassemia in these individuals. HbA2 levels ≤2.5% is one of the indicators of α-thalassemia according to several studies [20,21]. This rate limit is not applicable to individuals with SCT, as we showed that AS individuals had a high level of HbA2.…”
Section: Hbs and Hba2 Levels And Thalassemia Frequenciesmentioning
confidence: 60%
“…Certain structural Hb variants may also reduce the level of HbA2 at varying degrees. 44 The patients with abnormally low HbA2 had higher levels of some minor components in areas designated for HbA1a, and HbA1b, HbA1c, which are post-translational modifications of the major haemoglobin component A0. Since HbSS individuals do not have HbA0, these may represent unidentified modified variants of HbS which compete with HbA2 for the alpha chain.…”
Section: Haemoglobins F and A2 In The Study Populationmentioning
confidence: 96%